Nursing concerns with palliative care and at the end-of-life in patients with heart failure - Westlake C; Smith VJ (Dove Medical Press, 2015)
Cheryl Westlake,1 Valerie Joy Smith2 1School of Nursing, Azusa Pacific University, Azusa, CA, USA; 2Department of Nursing, Keck Medical Center of University of Southern California, Los Angeles, CA, USA Abstract: Patients with chronic heart failure (HF) suffer from numerous symptoms and quality-of-life (QOL) concerns, and thus, palliative care, a multidisciplinary approach that includes the family and focuses on the improvement of patients' and their families' QOL through the relief of physical, psychosocial, and spiritual suffering, is needed. The transition to hospice care is made when HF is refractory to medical therapy or when the potential harm of treatment outweighs the potential benefits. Nurses are key persons for patients with HF as they may initiate and support palliative and hospice care, focus on delivering patients' goal-directed, well-coordinated care, champion patients' and caregivers' needs, and facilitate optimal QOL. Despite the inclusion of palliative and hospice care for HF patients in published guidelines, health care providers are frequently unfamiliar with palliative and hospice care and the needs of HF patients and their families. Therefore, this paper addresses the nurses' role in determining for whom, and when palliative and hospice care is appropriate; where and how palliative and hospice care should be provided; and the communication needs of patients and their families regarding referral to hospice, emergencies, implantable cardioverter-defibrillator therapy, ventricular assist devices, and continuous intravenous inotropic or vasoactive support at the end-of-life. Keywords: palliative care, hospice care, end of life care, palliative care nursing, hospice care nursing, heart failure, heart failure therapy